1989
DOI: 10.1159/000150092
|View full text |Cite
|
Sign up to set email alerts
|

Amphibian and Piscine Iridoviruses Proposal for Nomenclature and Taxonomy Based on Molecular and Biological Properties

Abstract: We have compared a number of properties of the well-characterized iridovirus, frog virus 3, with two other iridoviruses from amphibia, bullfrog edema virus and Lucké triturus virus, and with a piscine iridovirus, goldfish virus (GFV), to provide information for developing taxonomic classification of these viruses and establishing their ecological niche. Purified virions had similar size and shape (icosahedral) for each virus, and the genomic DNAs of each virus were methylated by a virus-induced DNA methyltrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 14 publications
(21 reference statements)
0
23
0
Order By: Relevance
“…The isolate is similar in size, biological characteristics and CPE to ranaviruses isolated in North America (Essani & Granoff 1989). The North American ranaviruses 1, 2 and 3 will not replicate above 33 "C (Granoff et al 1965, Clark et al 1969, Gravell & Granoff 1970, Essani & Granoff 1989. The replication of the isolate from Limnodynastes ornatus showed a similar temperature sensitivity.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The isolate is similar in size, biological characteristics and CPE to ranaviruses isolated in North America (Essani & Granoff 1989). The North American ranaviruses 1, 2 and 3 will not replicate above 33 "C (Granoff et al 1965, Clark et al 1969, Gravell & Granoff 1970, Essani & Granoff 1989. The replication of the isolate from Limnodynastes ornatus showed a similar temperature sensitivity.…”
Section: Discussionmentioning
confidence: 80%
“…AZC inhibition of replication of the isolate indicates that DNA methylation is an essential process (Goorha et al 1984). The isolate is similar in size, biological characteristics and CPE to ranaviruses isolated in North America (Essani & Granoff 1989). The North American ranaviruses 1, 2 and 3 will not replicate above 33 "C (Granoff et al 1965, Clark et al 1969, Gravell & Granoff 1970, Essani & Granoff 1989.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Digestion of DNA from RRV infected cells with HindIII and XbaI showed profiles (Fig. 10) distinct from FV3, LT1, and other known ranaviruses (Essani and Granoff, 1989;Mao et al, 1997). To strengthen the suggestion that RRV is an iridovirus, DNA from RRV infected cells was digested with HpaII or MspI.…”
Section: Virus Characterizationmentioning
confidence: 93%
“…Recent studies have compared EHNV with iridoviruses from the sheatfish Silurus glanis, the catfish Ictalurus melas and FV3 (Hedrick et al 1992, Hengstberger et al 1993. These studies showed that EHNV, BIV and FV3 belonged to the genus Ranavirus as do the sheatfish and catfish viruses (Essani & Granoff 1989, Hedrick et al 1992, Hengstberger et al 1993.…”
Section: Introductionmentioning
confidence: 99%